Corpus of Publications for award of LL.D. - Charleton, Peter Mitchel (Trinity College Dublin. School of Law. Discipline of Law, 2026)
This is a series of publications from 1984 to 2025 demonstrating a lifetime commitment to scholarship. the book Charleton & McDermott's Criminal Law and Evidence, from 2020, is a major textbook on criminal law, here represented by the author's contribution to the general part of criminal law and to evidence. The earliest article comes from the Dublin University Law Journal in 1984 and concerns the dilemma faced when those who were sexually exploited by reason of a handicap could not give evidence without taking an oath to tell the truth, while taking that oath put them outside the protected category. The article 'Blasphemy - Religion Challenges Freedom of Speech', from 2017 Irish Judicial Studies Journal, concerns the history and development of the crime of blasphemy and argues for a modern replacement given the sensitivities of religious groups. The article 'Cuban Missiles - A Warning on the Uncertainty of War', from 2022 Irish Judicial Studies Journal, engages with Von Clausewitz's theory on the auto-dynamic nature of armed conflict. Finally, the article 'EU-Data Nullification', from the Cambridge Law Journal 2025, critiques unfettered judicial power and the harm done in the specific instance of illogical reasoning by the Court of Justice of the European Union in putting the protection of data as a right above that of life itself and in creating illogical exceptions.
Charleton & McDermott's Criminal Law and Evidence (book)(1) and articles on: protecting the mentally handicapped from sexual exploitation (2), blasphemy as religion challenging freedom of speech (3), the Cuban missiles crisis (4), and EU-data nullification (5).
APPROVED
Keywords: Criminal law theory; blasphemy; illogic in law; uncertainty of war; unfettered power of CJEU